PELAKSANAAN TUGAS RUKUN TETANGGA DAN RUKUN WARGA (RT/RW) KELURAHAN DELIMA PEKANBARU - Yanuardi "; Febri Yuliani, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Rukun Tetangga (RT) is a division of territory in Indonesia below Rukun Warga (RW). Rukun Tetangga is not including division of government administration, and the formation passes through the citizens meeting. It is formed for social service that fixed by Desa or Kelurahan. Rukun Tetangga is led by Ketua RT who chose by the citizens. An RT consists of a group of houses (head of family).Rukun Warga (RW) is a division of territory in Indonesia below Dusun or Lingkungan. Rukun Warga is not including division of government administration, and the formation passes through the citizens meeting. It is formed for social service that fixed by Desa or Kelurahan. An RW consist of some RT.Rukun Tetangga (RT) and Rukun Warga (RW) are social organizations that established and built up of government to maintain and preserve the value of Indonesia social life based on work together and family principles and for helping increase the smoothness of government jobs, development and the sociality in the village and Kelurahan. Every RT consist of the most of 30 KK (Head of Family) for village and the most of 50 KK (Head of Family) for Kelurahan. The formation of RT and RW are based on Permendagri No. 7/1983.Kelurahan is a work territory of Lurah as area instrument of Kabupaten / Kotamadya / Kota administrasi below Kecamatan. Territory in the government structure at Pekanbaru, Kelurahan is the smallest organization unit and the nearest is social life. The meaning, the top of spear in carrying out the area self-sufficient at Pekanbaru is prearranged by the leader role of Lurahs.In cultivating of the institutions to achieve the social service satisfaction there are some factors that influence RT/RW jobs, and Social service Statisfaction